Pemberdayaan Ibu Rumah Tangga Kelurahan Mampang Prapatan di Bank Sampah Mekar Sari - Yuwanda Nila Ariyani; Isna Rahmawati (Empower : Jurnal Pengembangan Masyarakat Islam, 2024)
The population density in Special Capital District of Jakarta brings an environmental problem such as increasing waste generation. One way to overcome the waste problem is by empowering the community through waste banks. The waste bank not only undertake waste management but also improves their customer skills. The aim of this study is to find out the strategies and results of empowering housewives through waste management at the Mekar Sari Waste Bank. This study uses descriptive qualitative methods. Data collection methods use observation, interview and documentation techniques. The results of the study show that the strategies implemented by the Mekar Sari Waste Bank are motivation, increasing awareness and capacity training, self-management, resource mobilization, and network building and development. The strategy implemented is able to empower housewives with the benefits obtained, namely developing individual capacity, increasing income and developing entrepreneurial skills, helping the Mampang Prapatan Subdistrict government in reducing the volume of waste transported to landfill and creating a clean and healthy environment, as well as strengthening social ties in society.